Ophiofolius B, a new sesquiterpene from Ophiopogon confertifolius - Vinh Hue et al, Nguyen Thi (Vietnam Journal of Chemistry, 2014)
From the methanolic extract of the roots of Ophiopogon confertifolius N. Tanaka (Convallariaceae) a new sesquiterpene named ophiofolius B (1) was isolated. Its structure was elucidated as 3-eudesmene-1a,11-diol by the spectroscopic experiments (1H-NMR, 13C-NMR, DEPT 90o, DEPT 135o, HSQC, HMBC, 1H-1H COSY, and ESI-MS).